Merchant sail Volume 4 - Fairburn, William Armstrong (Center Lovell, Maine Fairburn Marine Educational Foundation, 1945)
Unites States merchant sail in the China, Australia, Manila, and India trades; development of the schooner rig and its use in coastwise service; last days of deep-sea sail --
65016
Keywords: History -- United States